2018
DOI: 10.1039/c8ra02657b
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Ag-decorated g-C3N4 nanosheets as recyclable SERS substrates for CV and RhB detection

Abstract: In this study, g-C 3 N 4 /Ag hybrid nanostructures were fabricated by facilely decorating silver nanoparticles on atmosphere-treated g-C 3 N 4 and served as efficient SERS-active substrates. The observed significant SERS enhancement of crystal violet (CV) molecules on g-C 3 N 4 /Ag could be attributed to the high ability to concentrate target molecules through p-p stacking interactions and the near-field enhancement caused by the boosting SPR effect of the Ag NPs. The atmosphere and calcination time have a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…In Figure c, it was clearly shown that the SERS intensity of Ag NCs and Ag NDs active substrate is 10.70 and 3.50 times stronger than ITO substrate at characteristic peak of 1649 cm –1 , respectively, which originated from the mesoporous and hierarchical structure of Ag NCs providing rich active sites for the adsorption of RhB. In addition, Ag NCs shows the lowest detecting concentration is 10 –8 M for RhB on Ag NCs in SI Figure S6, which is better than other reported results. …”
Section: Resultsmentioning
confidence: 67%
“…In Figure c, it was clearly shown that the SERS intensity of Ag NCs and Ag NDs active substrate is 10.70 and 3.50 times stronger than ITO substrate at characteristic peak of 1649 cm –1 , respectively, which originated from the mesoporous and hierarchical structure of Ag NCs providing rich active sites for the adsorption of RhB. In addition, Ag NCs shows the lowest detecting concentration is 10 –8 M for RhB on Ag NCs in SI Figure S6, which is better than other reported results. …”
Section: Resultsmentioning
confidence: 67%
“…Interestingly, there is an apparent red shift in the range 450-550 nm for g-C3N4, which may be caused by increases in polymerization degree and p-plane conjugation [63]. After loading Ag NPs onto the surface of the g-C3N4, its visible-light harvesting capacity is significantly enhanced and a red shift of approximately 50 nm due to the SPR effect can be observed [64][65][66]. In addition, Ag NPs can act as an efficient electronic transmission channel, significantly enhancing the separation of the photoexcited charge carriers produced by g-C3N4 [67].…”
Section: Optical Propertiesmentioning
confidence: 97%
“…[14][15][16] Photodegradation of dye molecules has also been shown by using a xenon lamp. 17,18 However, the molecules degraded quickly at high intensity irradiation of 100 mW cm À2 . The charge transfer enhancement mechanism has been rarely studied.…”
Section: Introductionmentioning
confidence: 99%